2006
DOI: 10.1002/humu.20315
|View full text |Cite
|
Sign up to set email alerts
|

A homozygousZMPSTE24null mutation in combination with a heterozygous mutation in theLMNAgene causes Hutchinson-Gilford progeria syndrome (HGPS): insights into the pathophysiology of HGPS

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is a rare premature aging disorder normally caused by a spontaneous heterozygous mutation in the LMNA gene that codes for the nuclear lamina protein lamin A. Several enzymes are involved in the processing of its precursor, prelamin A, to the mature lamin A. A functional knockout of one of the enzymes involved in prelamin A processing, the zinc metalloprotease ZMPSTE24, causes an even more severe disorder with early neonatal death described as restrictive dermatopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 33 publications
4
50
0
4
Order By: Relevance
“…14 The second patient carried a homozygous ZMPSTE24 frameshift deletion associated with an LMNA heterozygous nonsense mutation that 'rescued' the patient's phenotype, most probably by reducing to half the amounts of accumulated prelamin A, as in the double-knockout Zmpste24 À/À Lmna +/À mice. 15,31 This patient showed features compatible with a severe form of MADB, but was described as being affected with HGPS. 15 In this last report, the authors concluded that the LMNA truncation is a salvage alteration modifying the clinical picture from RD to HGPS by preventing farnesylation of the accumulated prelamin A or by reducing the amount of accumulated prelamin A.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…14 The second patient carried a homozygous ZMPSTE24 frameshift deletion associated with an LMNA heterozygous nonsense mutation that 'rescued' the patient's phenotype, most probably by reducing to half the amounts of accumulated prelamin A, as in the double-knockout Zmpste24 À/À Lmna +/À mice. 15,31 This patient showed features compatible with a severe form of MADB, but was described as being affected with HGPS. 15 In this last report, the authors concluded that the LMNA truncation is a salvage alteration modifying the clinical picture from RD to HGPS by preventing farnesylation of the accumulated prelamin A or by reducing the amount of accumulated prelamin A.…”
Section: Discussionmentioning
confidence: 92%
“…15,31 This patient showed features compatible with a severe form of MADB, but was described as being affected with HGPS. 15 In this last report, the authors concluded that the LMNA truncation is a salvage alteration modifying the clinical picture from RD to HGPS by preventing farnesylation of the accumulated prelamin A or by reducing the amount of accumulated prelamin A. This second hypothesis is more probable from our point of view, as no truncated lamin A isoform was visible on the western blot.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The patient carried a homozygous ZMPSTE24 frame-shift mutation (p.Val402Serfs*2) associated with a LMNA nonsense mutation (p.Arg654*) acting as a salvage alteration alleviating the clinical picture from RD to HGPS-like. 26 Thill et al 17 presented an exception to the rule. They described a typical RD phenotype in a patient carrying only a heterozygous missense mutation (p.Leu462Arg).…”
Section: Pathogenicity Of Splice Site Mutationsmentioning
confidence: 99%
“…Other mutations were found in additional cases of RD [15][16][17][18][19][20][21] and progeroid syndromes phenotypically overlapping with MAD and HGPS that can be nosologically classified as MAD-B, given the common molecular basis, involving ZMPSTE24 deficiency. 13,[22][23][24][25][26][27][28] RD, MAD-B and HGPS share a common pathophysiological mechanism based on the abnormal accumulation of a wild type or modified lamin A precursors.…”
Section: Introductionmentioning
confidence: 99%